A gallium iodide / stannous iodide double-modified sodium solid-state electrolyte as well as a preparation method and application thereof
Patent Information
- Application Number
- CN202611468859.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]鉴于现有技术的上述缺点、不足,本发明提供一种碘化镓/碘化亚锡双修饰的钠固态电解质及其制备方法与应用,进而解决现有技术中负极侧钠金属使副产物堆积,进而破坏固态电池,并且在钠金属负极侧,还存在由于钠沉积不均匀造成的应力不均,导致循环过程中枝晶生长和不可逆“死钠”产生,失活的钠将不再参与反应,破坏固态界面,损害固态电池长期安全稳定运行的技术问题
(1)本发明利用碘化镓(GaI3)和碘化亚锡(SnI2)的强还原反应活性,在电池首次循环或加热组装过程中,与钠金属负极原位发生如下化学反应:
Smart Images

Figure CN123018111A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte preparation technology, and in particular to a gallium iodide / tin iodide dual-modified sodium solid electrolyte, its preparation method and application. Background Technology
[0002] Layered oxide solid electrolytes (Na2Mg2TeO6) are a new member of the oxide solid electrolyte family, successfully prepared by Chinese researchers in 2018. Layered oxide solid electrolytes offer advantages such as a wide voltage window, good air stability, and high safety. They also exhibit good compatibility with layered oxide cathode materials and exhibit a relatively small space charge layer effect during cycling, making Na2Mg2TeO6 a promising oxide solid electrolyte.
[0003] However, the interfacial stability of layered oxide solid electrolytes remains significantly insufficient. Although the positive electrode side interface can achieve better lattice matching and mitigation of space charge layers, the strong reducing power of sodium metal on the negative electrode side hinders the high-valence state of tellurium (Te) in Na2Mg2TeO6-based solid electrolytes. 6+ Or magnesium element Mg 2+ This poses a significant hazard, easily forming low-valence, high-electron-conductivity interface byproducts. As these byproducts accumulate, sodium dendrites grow and pierce the solid electrolyte, causing short circuits and severely damaging the solid-state battery. Furthermore, achieving a completely uniform and consistent contact between metallic sodium and the solid electrolyte is difficult, and the layered oxide solid electrolyte itself has low ionic conductivity (10⁻⁶). -5 S / cm-10 -4 The sodium ion transport rate is poor (S / cm), with poor kinetics and a large interfacial impedance on the sodium contact side, which severely restricts the sodium ion transport rate.
[0004] On the sodium metal anode side, existing interface problems also include stress unevenness caused by uneven sodium deposition, which leads to dendrite growth and irreversible "dead sodium" generation during cycling. These deactivated sodiums will no longer participate in the reaction and will continue to accumulate with cycling, damaging the solid-state interface and impairing the long-term safe and stable operation of solid-state batteries.
[0005] Therefore, the present invention provides a sodium solid electrolyte with gallium iodide / tin iodide dual modification, its preparation method and application. Summary of the Invention
[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a sodium solid electrolyte with gallium iodide / tin iodide dual modification, its preparation method and application, thereby solving the technical problems in the prior art where sodium metal on the negative electrode side causes by-product accumulation, which in turn damages the solid-state battery. Furthermore, on the sodium metal negative electrode side, there is also the problem of stress unevenness caused by uneven sodium deposition, which leads to dendrite growth and irreversible "dead sodium" generation during cycling. The deactivated sodium will no longer participate in the reaction, damaging the solid interface and impairing the long-term safe and stable operation of the solid-state battery.
[0007] To achieve the above objectives, the first aspect of the present invention provides a sodium solid electrolyte with gallium iodide / tin iodide dual modification, the surface of which has an iodide coating formed by gallium iodide (GaI3) and tin iodide (SnI2).
[0008] Alternatively, the iodide coating is obtained by dissolving gallium iodide and tin iodide in an organic solvent to form a solution, coating it onto the surface of a solid electrolyte, and then drying it in situ.
[0009] Optional organic solvents include a mixture of ethylene glycol dimethyl ether and N,N-dimethylformamide, with a volume ratio of ethylene glycol dimethyl ether to N,N-dimethylformamide of 9:1; gallium iodide content in the solution is 0.05 g / 10 ml to 0.2 g / 10 ml, and stannous iodide content in the solution is 0.02 g / 10 ml to 0.1 g / 10 ml.
[0010] Optionally, the preferred ratio of gallium iodide to tin iodide is 0.1g:0.03g (solvent is 10ml DME).
[0011] A second aspect of this invention provides a method for preparing a gallium iodide / tin iodide dual-modified sodium solid electrolyte, comprising: Step 1: Using anhydrous sodium carbonate, magnesium oxide, and tellurium dioxide as raw materials, the mixture is prepared according to the stoichiometric ratio of Na2Mg2TeO6. After ball milling, pre-sintering, and ball milling again, it is pressed into shape and calcined at high temperature to obtain Na2Mg2TeO6 solid electrolyte ceramic sheets. Step 2: Dissolve gallium iodide and stannous iodide in an organic solvent to obtain an iodide solution; Step 3: The iodide solution from Step 2 is dropped onto the surface of the solid electrolyte ceramic sheet from Step 1, and then dried in situ to obtain a sodium solid electrolyte with gallium iodide / tin iodide dual modification.
[0012] Optionally, in step 1: the pre-sintering temperature is 700℃, the high-temperature calcination temperature is 800℃-900℃, the calcination time is 6h, and the pressing pressure is 6 tons; the molar ratio of anhydrous sodium carbonate, magnesium oxide, and tellurium dioxide, calculated as Na, Mg, and Te, is Na:Mg:Te = 2:2:1.
[0013] Optionally, in step 2: the amount of gallium iodide is 0.05g-0.2g, the amount of stannous iodide is 0.02g-0.1g, and 10ml of organic solvent of ethylene glycol dimethyl ether and N,N-dimethylformamide is added. The mixture is then magnetically stirred overnight until completely dissolved.
[0014] Alternatively, in step 3: the amount of iodide solution added is 30 μL, the in-situ drying temperature is 50 °C, and the drying time is 12 h.
[0015] The third aspect of the present invention provides an application of a sodium solid electrolyte modified with gallium iodide / tin iodide in a sodium metal secondary battery, the sodium metal secondary battery comprising a positive electrode, a negative electrode and a sodium solid electrolyte.
[0016] The beneficial effects of this invention are: (1) This invention utilizes the strong reducing reactivity of gallium iodide (GaI3) and tin iodide (SnI2) to conduct the following chemical reaction with the sodium metal anode in situ during the first cycle or heating assembly of the battery: GaI3+3Na→Ga+3NaI; SnI2 + 2Na → Sn + 2NaI; xNa + yGa → Na x Ga y (Sodium-gallium alloy); xNa+ySn→Na x Sn y (Sodium-tin alloy); The NaI produced by the reaction has a high ionic conductivity (10). -5 With a conductivity on the order of S / cm and extremely low electronic conductivity, a dense fast ion conduction layer is formed in situ, effectively isolating sodium metal from direct contact with the Na2Mg2TeO6 solid electrolyte and suppressing the Te... 6+ / Mg 2+ The risk of being reduced to generate highly electron-conducting byproducts.
[0017] (2) The semi-liquid sodium-gallium alloy has a low sodium deposition overpotential, which can preferentially guide the uniform deposition of sodium metal at nucleation sites, avoiding local charge accumulation. At the same time, the sodium-tin alloy, as a rigid framework, has good sodium affinity and structural stability, which can anchor the liquid sodium-gallium alloy and prevent it from agglomerating or leaking during long-term cycling, forming a composite structure of "flexible semi-liquid ion channel + rigid anchoring framework". This structure synergistically homogenizes the electric field distribution and ion current density at the interface, and suppresses the tip growth effect of sodium dendrites.
[0018] (3) During long-term cycling, some sodium metal becomes electrochemically inert "dead sodium" due to loss of electrical contact. The I present in the interface layer of this invention...- The ions have high electronegativity and oxidizing power, and can react with dead sodium (Na+I) under the drive of an electric field. - →NaI+e - This reactivates deactivated sodium into electrochemically active Na+. + By participating in subsequent cycles, it effectively mitigates interface deterioration caused by the accumulation of "dead sodium," improves the utilization rate of sodium metal, and further extends the cycle life of the battery.
[0019] (4) The application of the gallium iodide / tin iodide dual-modified sodium solid electrolyte of the present invention in sodium metal secondary batteries, wherein the iodide coating reacts in situ with the sodium metal negative electrode during battery cycling to generate sodium iodide, sodium gallium alloy and sodium tin alloy, thereby enabling sodium iodide to act as a fast ion conduction layer, sodium gallium alloy / gallium metal to provide a semi-liquid ion fast channel and sodium deposition site, and sodium tin alloy to provide a rigid skeleton anchoring effect. The three work together to reduce interface impedance and promote uniform sodium deposition. That is, after gallium iodide / tin iodide dual modification, the interface contact between the electrode and the electrolyte is more stable, effectively suppressing sodium dendrite puncture, thereby significantly extending the cycle life of the battery.
[0020] (5) In this invention, gallium iodide and tin iodide are dissolved in ethylene glycol dimethyl ether (DME) and N,N-dimethylformamide (DMF) (volume ratio DME:DMF=9:1). The modification can be completed by drop coating and low-temperature in-situ drying (50°C). The process is simple and the conditions are mild. It is highly compatible with existing solid electrolyte preparation processes, does not require expensive equipment or complex atmosphere control, and is easy to scale up for production. Attached Figure Description
[0021] Figure 1 This is a comparison diagram of the symmetrical long-cycle performance of sodium solid electrolytes in Example 1 and Comparative Example 3; Figure 2 XRD comparison images of the solid electrolytes prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3; Figure 3 Figure 1 shows the sodium solid electrolyte prepared in Example 1 and Comparative Example 3, and the schematic diagram of sodium metal wettability. Figure 2 shows the solid electrolyte of Example 1, Figure 3 shows the sodium metal wettability of Example 1, Figure 4 shows the solid electrolyte of Comparative Example 3, and Figure 5 shows the sodium metal wettability of Comparative Example 3. Figure 4 The above are XPS comparison images of the coating side of the solid electrolyte before and after cycling in Example 1. In Figure (a), it is a schematic diagram of the iodine spectrum before cycling, Figure (b) is a schematic diagram of the iodine spectrum after cycling, Figure (c) is a schematic diagram of the sodium spectrum before cycling, and Figure (d) is a schematic diagram of the sodium spectrum after cycling. Figure 5This is a comparison chart of the Tafel test results for sodium solid electrolytes in Example 1 and Comparative Example 3; Figure 6 This is a comparison chart of the rate test results of solid electrolyte full cells in Example 1 and Comparative Example 3 (the positive electrode is NVP, and the negative electrode is sodium metal). Detailed Implementation
[0022] To better understand the above technical solutions, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the present invention can be understood more clearly and thoroughly, and that the scope of the present invention can be fully conveyed to those skilled in the art.
[0023] Example 1 (Preferred Ratio) Prepare Na2Mg2TeO6 solid electrolyte with gallium iodide / tin iodide dual modification.
[0024] Step 1, Preparation of Na2Mg2TeO6 substrate: The molar ratio of anhydrous sodium carbonate, magnesium oxide, and tellurium dioxide, calculated as Na, Mg, and Te, is Na:Mg:Te = 2:2:1. The mixture is prepared, ball-milled at 400 rpm for 12 hours, pre-fired at 700℃ for 12 hours, and ball-milled again for 12 hours. 0.3 g of powder is then placed in a 14 mm mold, pressed into a sheet under 6 tons of pressure, and embedded and sintered at 850℃ for 6 hours to obtain Na2Mg2TeO6 solid electrolyte ceramic sheet.
[0025] Step 2, preparation of iodide solution: In a glove box, dissolve 0.10 g gallium iodide (GaI3) and 0.03 g tin iodide (SnI2) in 10 mL of organic solvent DME and DMF, and stir magnetically overnight until completely dissolved to obtain a light yellow transparent iodide solution.
[0026] Step 3, Coating and Drying: Place the Na2Mg2TeO6 ceramic sheet on a 50℃ heating stage, and use a pipette to draw 30μL of the above iodide solution and evenly drop it onto the surface of the ceramic sheet. Keep it at 50℃ and dry in situ for 12h to obtain the sodium solid electrolyte with gallium iodide / tin iodide double modification, denoted as GSI-Na2Mg2TeO6.
[0027] like Figure 1 As shown, the obtained gallium iodide / tin iodide dual-modified sodium solid electrolyte was assembled into a sodium metal secondary battery, achieving a speed of 0.1 mA / cm². 2 0.1mAh / cm 2Constant current charge-discharge tests were conducted under these conditions, and the cycle stability time exceeded 220 hours. Among them, the sodium metal secondary battery of Comparative Example 3 (gray curve) experienced severe voltage fluctuations after approximately 90 hours of cycling (i.e., a short circuit or interface failure occurred, preventing further cycling). In contrast, the sodium metal secondary battery of Example 1 (orange curve) maintained stable cycling even after the gray curve failed, continuing for over 220 hours without showing any signs of a short circuit. Clearly, the modified layer in Example 1 significantly improved interface stability and suppressed dendrite growth. Throughout the cycling process, the voltage curve was very smooth and the amplitude (polarization voltage) remained stable, indicating that after gallium iodide / tin iodide dual modification, the interface contact between the electrode and electrolyte was more stable, effectively suppressing sodium dendrite penetration and thus significantly extending the battery's cycle life. In contrast, before failure, the gray curve of Comparative Example 3 showed a relatively large and fluctuating polarization voltage (the upper and lower amplitude of the curve), indicating high and unstable interface impedance. In other words, in Example 1, the sodium iodide, sodium gallium alloy layer and sodium tin alloy framework formed by gallium iodide / tin iodide dual modification jointly anchored and generated a flexible interface, a rapidly deposited channel and a sodium iodide fast ion layer, which together reduced the polarization voltage.
[0028] Comparative Example 1 (Single Gallium Iodide Modification) The difference from Example 1 is that only 0.10 g of gallium iodide was added to the solution, and tin iodide was not added; the remaining steps were exactly the same. The semi-liquid Na-Ga alloy can fill the microscopic voids at the interface, improving the solid-solid point contact to a surface contact. Therefore, the interface impedance decreased from 650 Ω·cm in Comparative Example 3. 2 Reduced to 200 Ω·cm in Comparative Example 1 2 The resulting GaI3-Na2Mg2TeO6 electrolyte also generates NaI and sodium-gallium alloy during the initial cycle. However, due to the lack of a rigid sodium-tin alloy framework, the semi-liquid sodium-gallium alloy gradually agglomerates and leaks during cycling, leading to deterioration of the interfacial contact (0.1 mA / cm). 2 The cycle life is approximately 1200 hours, which is significantly lower than the dual-modified system in Example 1 (2000 hours).
[0029] Comparative Example 2 (Single stannous iodide modification) The difference from Example 1 is that only 0.03 g of stannous iodide was added to the solution, without adding gallium iodide; the remaining steps were exactly the same. The resulting SnI2-Na2Mg2TeO6 electrolyte can form NaI and a sodium-tin alloy, but due to the lack of filling and self-healing effects of the semi-liquid sodium-gallium alloy, a large number of microscopic voids still exist at the solid-solid interface, with an interfacial impedance of 320 Ω·cm. 2 Although lower than the unmodified sample, it is much higher than the double-modified sample. 0.1 mA / cm 2With a cycle life of approximately 900 hours, the sodium-gallium alloy further validates its core role in improving interfacial contact and homogenizing deposition.
[0030] Comparative Example 3 (Unmodified Na2Mg2TeO6, abbreviated as NMTO) The Na₂Mg₂TeO₆ ceramic sheet prepared in Example 1 was used directly without any surface modification. A Na|Na₂Mg₂TeO₆|Na symmetric cell was assembled, and under the same testing conditions, the interfacial impedance reached as high as 650 Ω·cm. 2 0.1mA / cm 2 The circuit shorted due to dendrite puncture after only about 650 hours of cycling, which confirms the necessity of iodide modification.
[0031] Comparative Example 4 (High Concentration of Gallium Iodide) The only difference from Example 1 is that the amount of gallium iodide is 0.30g and the amount of tin iodide is 0.05g, while the rest of the steps are the same as in Example 1.
[0032] The resulting gallium iodide / tin iodide dual-modified sodium solid electrolyte exhibits increased NaI formation at the interface and lower initial interfacial impedance (100 Ω·cm). 2 However, during the reaction, excessive GaI3 led to excessive sodium consumption and the generation of iodine which shuttled to the positive electrode side, affecting the normal cycle of the positive electrode and resulting in a voltage drop of 0.2 mA / cm. 2 The stability of the cycle is slightly inferior to that of Example 1 (cycle life of about 1000h).
[0033] Comparative Example 5 (High Concentration of Stannous Iodide) The only difference from Example 1 is that the amount of gallium iodide is 0.08g and the amount of tin iodide is 0.15g, while the rest of the steps are the same as in Example 1.
[0034] In the obtained gallium iodide / tin iodide dual-modified sodium solid electrolyte, the proportion of sodium-tin alloy framework is increased, the interface rigidity is enhanced, and the interface impedance is 200 Ω·cm. 2 Slightly higher than 120 Ω·cm in Example 1 2 However, due to the significant anchoring effect of the skeleton, it exhibits better structural stability during high-temperature (60℃) cycling, with a stability of 0.5 mA / cm². 2 No short circuit was detected during the next 700 hours of cycling.
[0035] Comparative Example 6 (Gallium iodide + Tin iodide physical coating, non-in-situ reaction) The difference from Example 1 is that GaI3 and SnI2 were first dissolved in organic solutions of DME and DMF, respectively, and dried on the surface of Na2Mg2TeO6. Subsequently, the coating was pre-decomposed by heat treatment at 300°C before battery assembly (i.e., non-in-situ reaction). The resulting electrolyte pre-formed Ga and Sn, but due to the lack of an in-situ reaction driven by sodium metal, a tight chemical bond, gradient interface, and iodine-induced NaI-rich SEI layer (Solid Electrolyte Interface, or SEI layer) could not be formed between the coating and the sodium anode. The interfacial impedance was 280 Ω·cm. 2 120 Ω·cm higher than in Example 1 2 Furthermore, the coating is easily peeled off during the cycle, and its lifespan is only about 700 hours.
[0036] Table 1. Comparison of solid electrolyte preparation methods between the examples and comparative examples.
[0037] Table 2 Comparison of solid electrolyte performance between the examples and comparative examples
[0038] Based on Tables 1 and 2 above, we can conclude that: Comparative Example 1 (Single GaI3 modification) During battery assembly or the first cycle, the single GaI3 modified layer reacts with sodium metal as follows: GaI3+3Na→Ga+3NaI; xNa + yGa → Na x Ga y (Sodium-gallium alloy); This system can generate a NaI fast ion-conducting layer and a semi-liquid Na-Ga alloy in situ. NaI has high ionic conductivity and extremely low electronic conductivity, which can effectively isolate electrons and suppress Te. 6+ / Mg 2+ Reduced; the semi-liquid Na-Ga alloy can fill the microscopic voids at the interface, improving the solid-solid point contact to a surface contact, thus reducing the interfacial impedance from 650 Ω·cm. 2 Reduced to 200Ω·cm 2However, this system lacks a rigid Na-Sn alloy framework. Although the semi-liquid Na-Ga alloy initially fills the interface well, its fluidity leads to gradual aggregation, migration, and loss during hundreds of hours of cycling, driven by electric field forces, stress, and concentration gradients. This results in the reappearance of microscopic voids in the previously filled interface region. The reappearance of these voids reduces the solid-solid contact area again, gradually increases the interfacial impedance, and causes uneven local sodium ion concentration, ultimately leading to preferential nucleation and growth of sodium dendrites in the void regions. Therefore, the cycle life of Comparative Example 1 is only 1200 hours, significantly lower than the 2000 hours of Example 1.
[0039] Comparative Example 2 (Single SnI2 Modification) A single SnI2 modified layer reacts with sodium metal as follows: SnI2 + 2Na → Sn + 2NaI; xNa+ySn→Na x Sn y (Sodium-tin alloy); This system can generate a NaI fast ion-conducting layer and a Na-Sn rigid framework, both of which contribute to the improvement of interfacial stability: the NaI layer blocks electronic conduction, while the Na-Sn alloy framework provides structural support and sodium-loving nucleation sites, thus reducing the impedance from 650 Ω·cm. 2 Reduced to 320Ω·cm 2 However, this system lacks a semi-liquid Na-Ga alloy as an adaptive filling medium. Regardless of the modification, the surface of the solid electrolyte ceramic sheet inevitably exhibits microscopic unevenness (roughness typically in the submicron to micron range). Without a semi-liquid alloy filling, the contact between the Na-Sn rigid framework and the electrolyte surface, and between the framework and sodium metal, remains a rigid-rigid contact, resulting in a large number of microscopic voids that cannot be effectively filled, leading to discontinuous ion transport channels. The concentrated local current density at these voids also induces preferential nucleation of sodium dendrites at the void edges.
[0040] Furthermore, although the Na-Sn alloy framework is sodium-loving, the lack of a flexible component to buffer the stress generated by volume changes during repeated sodium deposition / stripping cannot be effectively absorbed, leading to stress concentration at the interface and accelerating its mechanical degradation. Therefore, although the cycle life of this system (900h) is better than that of the unmodified sample (650h), it is still far lower than that of the double-modified sample in Example 1 (>2000h).
[0041] Comparative Example 3 (unmodified) When unmodified Na₂Mg₂TeO₆ solid electrolyte comes into direct contact with a sodium metal anode, the sodium metal, due to its strong reducing properties, reacts with the high-valence Te atoms in the electrolyte. 6+ and Mg2+ The following side reactions occur: Te 6+ +4e - →Te 4+ (or metallic telluride Te) 0 ); The Te produced by the above reaction 4+ and Te 0 The high electronic conductivity creates an electronic conductive path at the interface, leading to continuous reduction of sodium metal and accumulation of byproducts. As the cycle continues, these highly conductive byproducts form leakage channels, preventing uniform sodium ion transport at the interface, resulting in localized current density concentration and inducing the growth of sodium dendrite tips. Dendrites penetrate the solid electrolyte ceramic sheet along grain boundaries or microcracks, ultimately causing an internal short circuit (occurring at 650 hours). Furthermore, the unmodified solid electrolyte ceramic sheet has a rigid inorganic plane surface, resulting in a solid-solid point contact with sodium metal. This limited contact area and high porosity create numerous micropores that become "dead zones" for ion transport, leading to extremely high interfacial impedance (650 Ω·cm). 2 This severely restricts the transport rate of sodium ions across the interface.
[0042] like Figure 2 As shown, the iodide formation in Example 1 (GaI3 / SnI2 dual modification) is uniform and clearly visible in the XRD pattern, proving that a uniform iodide interface coating can be obtained through solution modification. The XRD patterns of Examples 1 and Comparative Examples 1-2, compared with those of gallium iodide and tin iodide, clearly show consistent peak positions. Furthermore, compared to Comparative Example 3, only the interface iodide modification occurred, without affecting the internal crystal structure of the substrate. The modification only acted on the ceramic sheet surface, maintaining the intrinsic crystal framework and ion conduction pathways of the substrate electrolyte, confirming the success of the interface modification in Example 1.
[0043] Specifically, in Figure 3 The wettability of sodium metal on the electrolyte surface was clearly compared before and after modification. In Comparative Example 3, the unmodified Na2Mg2TeO6 surface showed sodium metal aggregated in a spherical pattern, indicating high interfacial energy, non-wetting, and that the matrix material was not sodium-affinity. The contact angle was 140°. (See [reference]). Figure 3 Figures (c) and (d) are shown in Figure 1; however, in Example 1, after modification with gallium iodide / tin iodide, the sodium metal spreads uniformly, indicating a significant improvement in wettability, with a contact angle of only 30°. See Figure 2. Figure 3 As shown in Figures (a) and (b), the interface performance is significantly improved, which leads to the difference in interface impedance, interface exchange current density, etc. between Example 1 and Comparative Example 3.
[0044] like Figure 4 As shown, in the XPS plots of Example 1 before and after the loop, byFigure 4 Figure (a) shows the peak position of iodide GaI3 / SnI2 before cycling, proving uniform iodide modification before cycling. Figure 4 Figure (b) shows the uniform formation of sodium iodide (the binding energy of iodine species shifts to lower binding energies, resulting in a decrease in overall strength). Furthermore, through... Figure 4 The comparison between Figure (c) and Figure (d) fully demonstrates the change in the overall iodide environment of the material, proving that the modified electrolyte and sodium metal are in situ in contact, and that sufficient reaction is achieved during the cycling process, forming a sodium iodide-rich SEI layer.
[0045] like Figure 5 As shown, by comparing the Tafel curves of Example 1 and Comparative Example 3, in terms of interfacial dynamics, due to the formation of the bimetallic alloy, a sodium-loving interface with low interfacial impedance and a sodium iodide-rich SEI layer are generated, which reduces the exchange current density from 9.4 × 10⁻⁶ in Comparative Example 3. -4 mA cm -1 Increased to 8.9 × 10 in Example 1 -3 mA cm -1 .
[0046] like Figure 6 As shown, the full-cell rate tests (positive electrode: NVP, negative electrode: sodium metal) of Example 1 and Comparative Example 3 verified the cycling potential of the full cell and the modification of the interface layer by the stable sodium iodide-rich SEI. It is evident that the product of Example 1 (NMTO-GSI) showed significant improvements in both rate performance and stability. For example, at a 0.5c rate cycle, the specific capacity of the product of Example 1 remained at 100 mAh g⁻¹. -1 Meanwhile, the product in comparison ratio 3 has dropped to 80mAh g. -1 the following.
[0047] Comparative Example 4 (GaI3=0.30g, out of range) When the amount of GaI3 is increased to 0.30 g / 10 mL (exceeding the upper limit of the claim by 0.2 g by 50%), the amount of Ga metal generated increases dramatically. According to the reaction GaI3 + 3Na → Ga + 3NaI, the amount of GaI3 increases by 3 times (compared to 0.10 g in Example 1), and the amount of metallic Ga and Na-Ga alloy generated increases significantly.
[0048] The capacity far exceeds the anchoring capacity of the framework: The rigid framework of the Na-Sn alloy is limited in quantity (Sn is only 0.05g), far from sufficient to anchor such a large amount of semi-liquid Na-Ga alloy. This leads to excessive liquid alloy overflowing, agglomerating, and being lost during cycling, making it impossible to maintain a stable interface structure. The lost Ga alloy deposits at the interface edge, forming a "dead alloy" region with high electronic conductivity, which in turn becomes a leakage channel, accelerating battery failure. In addition, the transformation of multivalent iodine generated by iodine shuttle to the positive electrode side affects the normal sodium storage behavior of the positive electrode. Although the initial impedance is slightly lower due to the formation of a large amount of NaI (100Ω·cm), the overall performance is still significantly affected. 2 However, the cycle stability deteriorated sharply (1000h), far lower than that of Example 1 (>2000h), proving that the proportions of each component must be coordinated and that more is not necessarily better.
[0049] Comparative Example 5 (SnI2=0.15g, out of range) When the SnI2 dosage was increased to 0.15 g / 10 mL (exceeding the upper limit of the claims by 0.1 g, reaching 50%): The Na-Sn rigid framework was excessive, and the SnI2 dosage increased fivefold compared to Example 1 (from 0.03 g to 0.15 g), resulting in a large amount of Na-Sn alloy framework and excessively strong interface rigidity. The liquid channels were relatively insufficient; the GaI3 dosage was only 0.08 g, resulting in a limited amount of Na-Ga semi-liquid alloy, which could not fully fill the microscopic gaps between the excessive framework, and a large number of physical contact voids remained at the solid-solid interface. Ion conduction pathways were blocked, and Na… + The transmission path needs to bypass the rigid skeleton particles, increasing the tortuosity and significantly raising the impedance (200Ω·cm). 2 Therefore, the cycle life (700h) is even lower than that of the unmodified sample (650h with limited improvement). Obviously, the excessive rigid framework actually destroys the interface's adaptability and ion conduction efficiency.
[0050] Comparative Example 6 (Non-in-situ pre-reaction) Comparative Example 6 used the exact same amounts of GaI3 and SnI2 as Example 1, but the key difference lies in the different formation mechanism of the interface layer: Example 1 (In-situ Pre-reaction): After coating the electrolyte surface with GaI3 / SnI2, a reduction reaction driven by sodium metal gradually occurs during battery assembly and cycling, dynamically generating NaI and alloy components. During this process, Na... + At the interface, species such as Ga and Sn have a concentration gradient, and the resulting interface layer exhibits a gradual change in composition from the outside to the inside, resembling Na|NaI / alloy mixture|Na2Mg2TeO6. The components are tightly connected through chemical bonding, resulting in high interfacial bonding strength. Furthermore, the proportions of each component can be adaptively adjusted to respond to changes in the interfacial state during the cycling process.
[0051] In Comparative Example 6, after drying the GaI3 / SnI2 solution, a pre-heat treatment at 300°C was performed to completely decompose the coating into Ga and Sn (essentially leaving the metal). These pre-formed products were then "attached" to the electrolyte surface before assembling the battery. At this point, the interface lacked the in-situ reaction driving force of sodium metal, and no chemical bonding or diffusion bond was formed between the pre-formed products and the electrolyte surface; only physical stacking contact occurred. Furthermore, the pre-decomposition process completely separated Ga and Sn into their respective independent phases, making it impossible to form a Na-Ga-Sn ternary synergistic structure with gradient distribution characteristics during cycling.
[0052] Therefore, in Comparative Example 6, the adhesion between the physically stacked coating and the electrolyte is poor. Under the mechanical stress caused by volume expansion / contraction during cycling, the coating is prone to peeling and loses its interfacial protection function. Furthermore, the in-situ reaction interface of Example 1 can continuously "fine-tune" the proportions of each component according to the sodium deposition state during cycling (for example, when there is excessive local sodium deposition, the excess sodium can be consumed in-situ to generate more alloy to buffer stress); the non-in-situ interface is a "dead structure" and cannot self-regulate in response to changes in the interface state. In Comparative Example 6, the pre-decomposed Ga and Sn exist as independent particles, lacking the core-shell gradient distribution characteristic of the "NaI-encapsulated alloy" unique to in-situ reactions, and cannot form a continuous ternary synergistic network. This results in the low interfacial impedance (280 Ω·cm) of Comparative Example 6. 2 ) higher than Example 1 (120Ω·cm) 2 The cycle life (700h) was only slightly improved compared to the unmodified sample (650h), and was significantly lower than that of the in-situ double-modified system (>2000h).
[0053] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make modifications, alterations, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A sodium solid electrolyte dual-modified with gallium iodide / tin iodide, characterized in that, The matrix material of the solid electrolyte is Na2Mg2TeO6, and its surface has an iodide coating formed by gallium iodide and tin iodide.
2. The sodium solid electrolyte with gallium iodide / tin iodide dual modification according to claim 1, characterized in that, The iodide coating is obtained by dissolving gallium iodide and tin iodide in an organic solvent to form a solution, coating it onto the surface of a solid electrolyte, and then drying it in situ.
3. The sodium solid electrolyte with gallium iodide / tin iodide dual modification according to claim 2, characterized in that: The organic solvent includes a mixture of ethylene glycol dimethyl ether and N,N-dimethylformamide, wherein the volume ratio of ethylene glycol dimethyl ether to N,N-dimethylformamide is 9:1; The gallium iodide content in the solution is 0.05 g / 10 ml to 0.2 g / 10 ml; The concentration of stannous iodide in the solution is 0.02 g / 10 ml to 0.1 g / 10 ml.
4. The sodium solid electrolyte with gallium iodide / tin iodide dual modification according to claim 3, characterized in that, The preferred ratio of gallium iodide to tin iodide is 0.1g:0.03g.
5. A method for preparing a sodium solid electrolyte with gallium iodide / tin iodide dual modification as described in any one of claims 1 to 4, characterized in that, include: Step 1: Using anhydrous sodium carbonate, magnesium oxide, and tellurium dioxide as raw materials, the mixture is prepared according to the stoichiometric ratio of Na2Mg2TeO6. After ball milling, pre-sintering, and ball milling again, it is pressed into shape and calcined at high temperature to obtain Na2Mg2TeO6 solid electrolyte ceramic sheets. Step 2: Dissolve gallium iodide and stannous iodide in an organic solvent to obtain an iodide solution; Step 3: The iodide solution from Step 2 is dropped onto the surface of the solid electrolyte ceramic sheet from Step 1, and then dried in situ to obtain a sodium solid electrolyte with gallium iodide / tin iodide dual modification.
6. The method for preparing the gallium iodide / tin iodide dual-modified sodium solid electrolyte according to claim 5, characterized in that, In step 1: The pre-sintering temperature is 700℃, the high-temperature calcination temperature is 800℃-900℃, the calcination time is 6h, and the pressing pressure is 6 tons. The molar ratio of anhydrous sodium carbonate, magnesium oxide, and tellurium dioxide, expressed as Na, Mg, and Te, is Na:Mg:Te = 2:2:
1.
7. The method for preparing the gallium iodide / tin iodide dual-modified sodium solid electrolyte according to claim 5, characterized in that, In step 2: The amount of gallium iodide used is 0.05g-0.2g, the amount of stannous iodide used is 0.02g-0.1g, and 10ml of organic solvents of ethylene glycol dimethyl ether and N,N-dimethylformamide are added. Stir magnetically overnight until completely dissolved.
8. The method for preparing the gallium iodide / tin iodide dual-modified sodium solid electrolyte according to claim 5, characterized in that, In step 3: The amount of iodide solution added was 30 μL, the in-situ drying temperature was 50 °C, and the drying time was 12 h.
9. The application of a sodium solid electrolyte with gallium iodide / tin iodide dual modification as described in any one of claims 1 to 4 in a sodium metal secondary battery, characterized in that, The sodium metal secondary battery includes a positive electrode, a negative electrode, and the sodium solid electrolyte.
